Cognitive Processing Therapy for Childbirth-Related Posttraumatic Stress Disorder: A Case Report. Issue 1 (February 2023) - Gobin, Keisha C.; Boyd, Jenna E.; Green, Sheryl M.
Highlights: A case study using CPT for CB-PTSD tailored content to meet the unique needs of postpartum women. Following CPT for CB-PTSD, clinically significant outcomes were produced in both PTSD and depressive symptoms. Our modified version of CPT was highly acceptable to the participant in our case study. Our findings show initial support for CPT as a strong psychotherapeutic intervention option for targeting CB-PTSD. Abstract: Having a baby is a natural biological process and commonly considered a positive and exciting time in life. However, birth and the postpartum period also represent a vulnerable time for mental health and the development of posttraumatic stress disorder (PTSD) among women who are exposed to traumatic events during birth. Childbirth-related PTSD (CB-PTSD) is a relatively new and unique construct, associated with negative impacts to the mother, her infant, and family more broadly. Research investigating psychological interventions following traumatic births remains scant and no studies have evaluated cognitive processing therapy (CPT), a well-established and empirically supported psychological therapy, in the treatment of CB-PTSD. We conducted a case study using CPT for CB-PTSD, modifying the length of the traditional protocol to eight sessions, and tailoring the content to meet the unique needs of postpartum women. Following CPT for CB-PTSD, clinically significant and meaningful treatment outcomes were produced in both PTSD and depressive symptoms, with gains maintained at 1-month follow-up. Our modified version of CPT for CB-PTSD was also highly acceptable with the participant in our case study. These findings provide initial support for CPT as a strong psychotherapeutic intervention option for targeting CB-PTSD. Further research is necessary to examine this treatment and its acceptability with a larger sample.